Long noncoding RNA SRY-box transcription factor 2 overlapping transcript participates in Parkinson's disease by regulating the microRNA-942-5p/nuclear apoptosis-inducing factor 1 axis. Issue 1 (1st January 2021) - Guo, Yabi; Liu, Yanyang; Wang, Hong; Liu, Peijun
ABSTRACT: Parkinson's disease (PD) is a neurodegenerative disorder. Studies have shown that long noncoding RNA SRY-box transcription factor 2 overlapping transcript (lncRNA SOX2-OT) is highly expressed in PD patients, but its specific functions and mechanisms require further research. To address this gap, this study utilized an in vitro PD cell model induced by 1-methyl-4-phenylpyridinium (MPP + ). Cell viability, apoptosis, lactate dehydrogenase (LDH) activity, inflammatory factor secretion, and oxidative stress indicators were determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-dipheyltetrazolium bromide assay, LDH assay, flow cytometry, enzyme linked immunosorbent assay (ELISA), and corresponding kits, respectively. Gene and protein expression were measured using quantitative real-time-PCR and western blotting, respectively. The results indicated that microRNA-942-5p (miR-942-5p) was a direct target of lncRNA SOX2-OT and nuclear apoptosis-inducing factor 1 (NAIF1) was a direct target of miR-942-5p. The expression levels of lncRNA SOX2-OT and NAIF1 were increased, and miR-942-5p expression was decreased in SH-SY5Y cells following MPP + treatment. In addition, MPP + treatment reduced SH-SY5Y cell viability, increased apoptosis; increased cleaved caspase-3 protein expression and cleaved caspase-3/caspase-3 ratio; enhanced lactate dehydrogenase viability; increased tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and reactive oxygen species, and decreased superoxide dismutase activity in SH-SY5Y cells were inhibited by SOX2-OT-siRNA, and these inhibitions were reversed by miR-942-5p inhibitor. Moreover, the protective role of miR-942-5p mimic in MPP + -induced SH-SY5Y cells was eliminated by the NAIF1 plasmid. Overall, lncRNA SOX2-OT-mediated regulation of oxidative stress, inflammation, and neuronal apoptosis were directly controlled by the miR-942-5p/NAIF1 signal axis in MPP + -induced SH-SY5Y cells.